PEMANFAATAN KERTAS KARTON KEMASAN SEBAGAI PLAT CETAK UNTUK TEKNIK BLOCK PRINTING - Jiraya, Sisca Dewi; Sekar, Ahda Yunia (ATRAT: Jurnal Seni Rupa, 2021)
Paperboard is often found in distribution packaging such as cardboard, thick cardboard, packs of cigarette products and household products. In addition to being used as packaging paper, cardboard distribution has the potential to be used in the craft sector, such as a research entitled Canting Cap Made from Waste Paper Packaging Nurohmad's creations in Dusun Sawit, Panggungharjo, Sewon, Bantul which uses cardboard as a printing plate in batik technique as a transfer medium for batik wax. on the cloth. This shows that paperboard can be developed in block printing techniques, seeing the similarities between batik techniques and block printing techniques which both require a printing plate and can transfer motifs. This study uses qualitative methods through literature studies, observations, interviews and experiments in making printing plates. The final result of this research is to produce a block printing plate from cardboard packaging which will be applied to sheets of cloth used in the manufacture of fashion clothing. Keywords: Packaging Carton, Printing Plate, Block Printing----------------------------------------------------------------------------------------- Kertas karton kerap ditemukan pada kemasan distribusi seperti kardus, karton tebal, kemasan pak produk rokok, dan produk rumah tangga. Selain dimanfaatkan sebagai kertas kemasan distribusi karton memiliki potensi untuk digunakan pada bidang kriya seperti penelitian yang berjudul Canting Cap Berbahan Limbah Kertas Kemasan Kreasi Nurohmad Di Dusun Sawit, Panggungharjo, Sewon, Bantul yang menggunakan kertas karton sebagai plat cetak pada teknik batik sebagai media transfer lilin batik pada kain. Hal tersebut memperlihatkan bahwa kertas karton dapat dikembangkan pada teknik block printing, melihat adanya kemiripan teknik batik dan teknik block printing membutuhkan plat cetak dan dapat mentransfer motif. Penelitian ini menggunakan metode kualitatif melalui studi literatur, observasi, wawancara, dan eksperimen pembuatan plat cetak. Hasil akhir penelitian ini menghasilkan plat cetak block printing dari kertas karton kemasan yang akan diaplikasikan dalam lembaran kain yang digunakan dalam pembuatan busana fashion. Kata Kunci: Karton Kemasan, Plat Cetak, Block Printing